PARAMETRIC STUDY TO REDUCE DISPLACEMENT AND RESIDUAL STRESS DUE TO WELDING PROCESS USING FINITE ELEMENT SIMULATION - Raulinzha Nugraha, Ksatria
Welding, the process of fusing two plastic or metal components through melting, with or without additional molten material, is vital across various industries. It entails the application of heat, pressure, or both to create a durable joint, known as a weldment. In sectors like transportation, welding finds extensive use, notably in vehicles such as high-speed trains and dump trucks. However, this process can introduce residual stress and displacement, potentially compromising structural integrity. High-speed trains, exemplifying rapid land transportation, are integral to Indonesia's national train network expansion, with the Kereta Cepat Merah Putih (KCMP) being a key component. Unlike conventional trains, High-speed trains like KCMP feature aluminum structures, specifically employing 6061-T6 aluminum. Conversely, dump trucks, essential for heavy-load transportation, especially in mining, rely on sturdy designs, with SM400A being a preferred material. This study utilizes finite element simulation to explore the impact of welding parameters on displacement and residual stress in welded joints. The goal is to discern optimal welding conditions to mitigate these adverse effects, which is crucial for upholding structural reliability. The parametric investigation encompasses varying thickness, heat input, weld sequence, and boundary conditions. The study's insights promise to refine welding practices, enhancing structural performance and diminishing the likelihood of weld failure.